Need to intensify emergency obstetric care services in Nigeria - Perpetus C. Ibekwe (AOSIS, 2011)
Each year more than half a million women around the world die from complications of pregnancy and childbirth; this number has not declined substantially in over two decades. Ninety-nine percent of these deaths occur in the developing world; Africa and Asia together accounting for 95% of the maternal deaths. The life time risk of maternal death in sub-Saharan Africa is one in 16, while the risk in developed countries is one in 2800. In Nigeria, since the launching of the Safe Motherhood Initiative (SMI) in September 1990, overwhelming evidence suggests a trend towards an increasing rate of maternal mortality. Available data indicate that Nigeria now has the second highest rate of maternal mortality in the developing world. Officially, the maternal mortality rate (MMR) is estimated at 800 maternal deaths per 100,000 live births. However, institutional figures on MMRs are staggering and frightening - 2101 per 100,000 and 3380 per 100,000 from two centres in Nigeria. Whereas Nigeria makes up 2% of the world's population, it contributes about 10% of the global burden of maternal deaths. These deaths are unacceptably high even by African standard.